Proceedings of the 2014 International Conference on Quantitative InfraRed Thermography 2014
DOI: 10.21611/qirt.2014.148
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental parameters on the thermographic analysis of the building envelope

Abstract: Typically, thermographic measurements are used to analyze the building envelope in a qualitative way (e.g. detection of thermal bridges, missing insulation, etc.). Besides, thermography can also be used to obtain surface temperatures, which can give an indication of the thermal performance of the building envelope. In this paper the influence of the most important environmental parameters on the thermographic analysis of different wall types is examined using a multivariable parameter study. This results in gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In situ measurements can give more representative values [25,38,40,[45][46][47]51,61,71], but the use of such methods is affected by many factors, with environmental factors being the most important. In situ measurement methods require [45,46,48,51,53,65,94,120,143,145] (i) a high thermal gradient (𝑇 𝑖𝑛 − 𝑇 𝑜𝑢𝑡 >10 °C), (ii) a wind speed of 0-1 m/s, (iii) zero rainfall, and (iv) no solar radiation or other radiation sources to affect the wall of interest. Other factors, such as metrological errors and data analysis, are also assessed in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ measurements can give more representative values [25,38,40,[45][46][47]51,61,71], but the use of such methods is affected by many factors, with environmental factors being the most important. In situ measurement methods require [45,46,48,51,53,65,94,120,143,145] (i) a high thermal gradient (𝑇 𝑖𝑛 − 𝑇 𝑜𝑢𝑡 >10 °C), (ii) a wind speed of 0-1 m/s, (iii) zero rainfall, and (iv) no solar radiation or other radiation sources to affect the wall of interest. Other factors, such as metrological errors and data analysis, are also assessed in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Wind speeds <1m/s allow steady conditions to be guaranteed. Vijver et al [145] found that wind combined with a clear sky and solar irradiation strongly affect QIRT test results. Tests should therefore ideally be performed 2 h before dawn [46] and when (i) the difference between the internal and external air temperatures is 7-16 °C, (ii) the wind speed is 0.1-1 m/s, (iii) no rain is falling, and (iv) the wall has not been exposed to direct radiation (to avoid thermal inertia effects).…”
Section: Metrological Performance Test Conditions and Data Acquisitionmentioning
confidence: 99%
“…Implementation of quantitative IRT encompasses aspects relating to operating conditions (outdoor air temperature), thermophysical properties (the kappa value, also called the heat capacity per unit of area) and technical conditions (test duration and data acquisition interval) [50,51,52,36,39,29,25,53,34,54,55]. In previous studies conducted in laboratories or experimental rooms, the first two aspects might be considered a source of discrepancy in the determination of the measured U-value, regardless of the technique that has been undertaken (simulation, climatic chamber or HFM) [29,31,33,55].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases the differences between indoor and outdoor temperature and the thermal properties of the walls under inspection (e.g. thermal conductivity, thermal mass, and surface emissivity) should be known or estimated 10 . Thermography could be applied in passive or active configuration, depending whether the analyzed element is stimulated by an external thermal source 11 .…”
Section: Introductionmentioning
confidence: 99%